Penerapan model pembelajaran connecting, organizing, reflecting, extending (core) untuk meningkatkan kemampuan berpikir kritis materi kegiatan ekonomi pada peserta didik kelas v sekolah dasar - Sutrisno, Ari Ardi; Winarni, Retno; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2019)
The purpose of this study to improve the ability to think critically on the material of economic activities by applying the Connecting, Organizing, Reflecting, Extending (CORE) learning model for 5th grade students of Elementary School students at semarang on 2018/2019, totalling 21 students. The procedure of this research consisted of 2 cycle, each cycle consisted of 2 learning process. Data collection on this research was done by observating, interviewing, critical thinking testing, and documentating. This research used interactive analysis (Miles and Huberman model) for analyse the research’s data. Based on the results of the study showed that the pre-action class average score was 58.29 (28.57%), it increased to 63,1 (60%) in the first cycle, and it increased to 73.79 (80.95%). Based on the above data it can be concluded that the application of the connecting, organizing, reflecting, extending (CORE) learning models can improve the critical thinking skills of economic activity material in fifth grade students.